Analysis of the front-crawl swimming performance factors using the MAD-system: Science meets practice - Toussaint, H. M. (First international symposium sciences and practices in swimming, 2006)
Essential performance-determining factors in front crawl swimming can be analysed within a biomechanical framework, in reference to the physiological basis of performance and using the MAD-system. Swimming fast will depend on 1. the ability to produce a high mechanical power Output enabling the generation of high propulsive forces, 2. the ability to reduce drag, while 3. keeping power losses to pushed away water (Pk) low, i.e. swimming with a high propulsive efficiency. Each of these performance factors can be determined and the changes over time with training can be monitored.